Fixed Point Theorems for Mappings Satisfying a Contractive Condition of Rational Expression on a Ordered Partial Metric Space: V. Pragadeeswarar, M. Marudai - Team, Support (Thai Journal of Mathematics, 2014)
The purpose of this manuscript is to present a fixed point theorem using a contractive condition of rational expression in the context of ordered partial metric spaces.